Latent microsporidiosis caused by Encephalitozoon cuniculi in immunocompetent hosts: a murine model demonstrating the ineffectiveness of the immune system and treatment with albendazole - Kotkova, Michaela; Sak, Bohumil; Kvetonova, Dana; Kvac, Martin (PLoS One, 2013)
BACKGROUND: Microsporidia are obligate intracellular parasites causing severe infections with lethal outcome in immunocompromised hosts. However, these pathogens are more frequently reported as latent infections in immunocompetent individuals and raises questions about the potential risk of reactivation following induced immunosuppression. AIMS: To evaluate the possibility latent microsporidiosis, efficacy or albendazole, and reactivation, the authors monitored the course of E. cuniculi infection in immunocompetent BALB/c mice and immunodeficient SCID mice using molecular methods. METHODS: Mice were per orally infected with 10(7) spores of E. cuniculi. Selected groups were treated with albendazole, re-infected or chemically immunosuppressed by dexamethasone. The presence of microsporidia in the host's organs and feces were determined using PCR methods. Changes in numbers of lymphocytes in blood and in spleen after induction of immunosuppression were confirmed using flow cytometry analysis. RESULTS: Whereas E. cuniculi caused lethal microsporidiosis in SCID mice, the infection in BABL/c mice remained asymptomatic despite parasite dissemination into many organs during the acute infection phase. Albendazole treatment led to microsporidia elimination from organs in BALB/c mice. In SCID mice, however, only a temporary reduction in number of affected organs was observed and infection re-established post-treatment. Dexamethasone treatment resulted in a chronic microsporidia infection disseminating into most organs in BALB/c mice. Although the presence of E. cuniculi in organs of albendazole- treated mice was undetectable by PCR, it was striking that infection was reactivated by immunosuppression treatment. CONCLUSION: Our results demonstrated that microsporidia can successfully survive in organs of immunocompetent hosts and are able to reactivate from undetectable levels and spread within these hosts after induction of immunosuppression. These findings stress the danger of latent microsporidiosis as a life-threatening risk factor especially for individuals undergoing chemotherapy and in transplant recipients of organs originating from infected donors.
Keywords: Feces; Viscera; Disease Models, Animal; polymerázová řetězová reakce; myši SCID; Mice, Inbred BALB C; Vero Cells; zvířata; Cercopithecus aethiops; feces; albendazol; průtoková cytometrie; myši inbrední BALB C; Mice, SCID; Dexamethasone; modely nemocí na zvířatech; Polymerase Chain Reaction; encephalitozoonóza; Encephalitozoon cuniculi; Flow Cytometry; Mice; Vero buňky; vnitřnosti; myši; dexamethason; Albendazole; Lymphocyte Count; Animals; Chlorocebus aethiops; Encephalitozoonosis; počet lymfocytů